Surgical nurses’ perceptions of patient aggression and exposure to workplace violence: a cross-sectional study - Müjgan Solak; Satı Doğan (BMC Nursing)
Abstract Background Nursing is the profession most affected by violence in healthcare institutions. This study aimed to investigate the perception of patient aggression and exposure to violence among nurses working in surgical departments. Methods This descriptive cross-sectional study was completed with 267 nurses working in surgical departments between February and June 2023. A personal questionnaire and the patient perception of aggression scale (POAS) were used as data collection tools. Results Results indicated that 76% of surgical nurses experienced violence, predominantly verbal, perpetrated by patients or their relatives. Most nurses (81.3%) reported feeling unsafe in their workplace. It was determined that the mean dysfunctional score of the nurses on the POAS scale was higher than the mean functional score. In the functional dimension, the department and number of patients showed a significant difference. In the dysfunctional dimension, the departments they worked in, and years of employment showed a significant difference (p < 0.05). Conclusions Workplace violence is prevalent among surgical nurses. It was determined that nurses were mostly exposed to violence by patients and their relatives, and that female nurses with high dysfunction scores were more exposed to violence.